Oral antibiotic prophylaxis in elective cesarean deliveries: pilot analysis in tertiary Care Hospital. (19th March 2021) - Keskin, Muge; Pabuccu, Emre Goksan; Sahin, Ozgur; Cakmak, Didem; Oral, Sezin; Kiseli, Mine; Yarcı Gursoy, Asli; Dincer Cengiz, Sevim
Abstract: Introduction: Puerperal infection remains a significant cause of maternal morbidity and mortality. Those infections occur more likely after cesarean delivery (CD). Prophylactic antibiotics are administered at the time of CD to prevent complications. In addition to intraoperative prophylaxis; prescription of antibiotics during hospital discharge to prevent surgical site infections (SSI) is quite common. Purpose of this study is to determine the utility of prophylactic oral antibiotic prescription in a cohort of low-risk women undergoing CD. Materials and methods: A prospective observational study was conducted between 2014 and 2018 at Ufuk University School of Medicine, Department of Obstetrics and Gynaecology. Total of 389 low risk elective cesarean deliveries were selected. All cases received intraoperative prophylaxis. In group I (157 subjects), no further antibiotics were given and in group II (232 cases), oral cephuroxime 500 mg was given during hospital discharge. Primary outcome was SSI. Secondary outcomes were endometritis and other infectious conditions. Results: Overall SSI rate was 2.5%. Only 2 SSIs were noted in group 1 (1.2%) compared to eight in group II (3.4%). There was no statistical difference in SSI rate between two groups. Secondary outcomes were also comparable. Conclusion: In this study, we failed to reveal any beneficial effect of oral antibiotic prescription during hospital discharge in low risk elective CDs. Therefore, use of oral antibiotics in addition to intraoperative prophylaxis should be questioned in terms of increased costs, emergence of bacterial resistance and long term effects on new born as a consequence of changes in gut microbiome.